2021
DOI: 10.1093/bib/bbab482
|View full text |Cite
|
Sign up to set email alerts
|

Identifying correlations driven by influential observations in large datasets

Abstract: Although high-throughput data allow researchers to interrogate thousands of variables simultaneously, it can also introduce a significant number of spurious results. Here we demonstrate that correlation analysis of large datasets can yield numerous false positives due to the presence of outliers that canonical methods fail to identify. We present Correlations Under The InfluencE (CUTIE), an open-source jackknifing-based method to detect such cases with both parametric and non-parametric correlation measures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To identify gut commensals that are associated with gut trypsin activity and EAE severity, we performed correlations under the influence (CUTIE) 44 correlation analysis on all the mice. We found that four Lactobacillus species including L. reuteri , L. frumenti , L. vaginalis , and L. f/r/a/o/p/v negatively correlated with trypsin activity and EAE severity during the pre-symptomatic phase of the disease ( Figures 4 A and 4C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify gut commensals that are associated with gut trypsin activity and EAE severity, we performed correlations under the influence (CUTIE) 44 correlation analysis on all the mice. We found that four Lactobacillus species including L. reuteri , L. frumenti , L. vaginalis , and L. f/r/a/o/p/v negatively correlated with trypsin activity and EAE severity during the pre-symptomatic phase of the disease ( Figures 4 A and 4C).…”
Section: Resultsmentioning
confidence: 99%
“… 71 http://rdp.cme.msu.edu ; RRID: SCR_022773 Resphera Insight (v2.2) Resphera Biosciences Shaikh et al., 2021 65 https://respherabio.com/ CUTIE (Correlations Under The InfluencE) Bu et al. 44 https://github.com/clemente-lab/CUTIE.git ImageJ Schneider et al. 72 https://imagej.net/ij/index.html ; RRID: SCR_003070 Prism v9.3.1 Graphpad Software https://www.graphpad.com/ ; RRID: SCR_002798 Other Illumina Inc. https://www.illumina.com/ …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation analysis with CRP and microbiome: Only sequence data with paired CRP measurements were included. Microbial relative abundances were correlated with CRP measurements using Correlations Under the Influence (CUTIE) 28 .…”
Section: Microbiota Analysesmentioning
confidence: 99%